(untitled) (Journal of Partial Differential Equations, 1992)
We prove C^1,α-partial regularity of weak solution of nonlinear parabolic systems u^i_t - D_αA^α_i(x, t, u, Du) = B_i(x, t, u, Du), i=1,…, N under the main assumption that A^α_i and B_i, satisfy the natural growth condition.